AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 96% KULIT PISANG RAJA (Musa paradisiaca L) TERHADAP Escherichia coli - Agnis Pondinekaria Aditama, Rizqiyah Akbar Mauliddah (AKADEMI FARMASI JEMBER, 2017)
Banana peel is a material that can be used as a natural antibacterial because of its secondary metabolites content. The present study aimed to evaluate antibacterial activity of ethanol 96% extracted from banana (Musa paradisiaca L) peel against Escherichia coli. Result of phytochemical screening indicated that banana peel extract has alkaloid, flavonoid (tannin), and saponin compound that can act as antibacterial. Banana peel extract showed antibacterial activity that was proved by clear zone formed around disk paper. Sample of 64% extract concentration had the largest inhibition zone (9.6 mm) compared to sample of 16% and 32% concentration, inhibition zone of which was 4.4 mm and 6.26 respectively. One Way Anova analysis showed that sample of 64% concentration was significantly different from negative control, 16%, and 32% concentration. Nevertheless, there was no significant difference between 16% and 32% concentration.Keywords: Musa paradisiaca L, Escherichia coli, antibacterial